2008
DOI: 10.1016/j.jvs.2008.02.070
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal artery-only runoff following endovascular revascularizations is effective for limb salvage in patients with tissue loss

Abstract: Endovascular revascularization with PAOR results in acceptable patency and limb salvage rates in patients presenting with tissue loss, and is equivalent to other vessel runoff for patency, limb salvage and wound healing rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 27 publications
3
24
0
1
Order By: Relevance
“…These findings, although limited by the small number of patients in the IR group, are in agreement with those reported by Dosluoglu et al [12] and document how the indirect treatment of the affected angiosome is an effective option in cases of a technical inability to use a DR.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings, although limited by the small number of patients in the IR group, are in agreement with those reported by Dosluoglu et al [12] and document how the indirect treatment of the affected angiosome is an effective option in cases of a technical inability to use a DR.…”
Section: Discussionsupporting
confidence: 92%
“…The primary goal of PTA treatment is to restore the patency of at least one below-the-knee (BTK) vessel, preferably the tributary of the anatomical region of the ulcer [9]. Several studies have demonstrated good results in terms of patency and limb salvage after endovascular treatment of diabetic foot [10][11][12][13][14]. Many, however, are limited by the presence of a heterogeneous population with different stages of ischemia (claudication, rest pain, trophic lesions) and different treatment modalities, with PTA performed both in the above-the-knee (ATK) and BTK areas [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although nonsignificant in our series, contralateral amputation as an independent predictor has been reported, with a 20% to 24% incidence of contralateral amputation in patients with limb loss, 1,2,22 and is likely a reflection of the overall poor general condition of these patients. The peroneal artery as the only runoff has been reported as being adequate after open and endovascular revascularizations for limb salvage [23][24][25][26] and was not associated with limb loss despite a patent revascularized segment in the multivariate analysis in our series.…”
Section: Discussionmentioning
confidence: 49%
“…Our technique for percutaneous interventions were previously described. 22 Patients typically received 5000 to 6000 U of heparin after a sheath was placed, which was not reversed at the end of the procedure. All patients were kept on clopidogrel 75 mg and enteric coated acetyl salicylic acid (ECASA) 81 mg for a minimum of 30 days, followed by lifelong ECASA.…”
Section: Methodsmentioning
confidence: 99%